2020
DOI: 10.1186/s12913-020-4924-1
|View full text |Cite
|
Sign up to set email alerts
|

“From taboo to routine”: a qualitative evaluation of a hospital-based advocacy intervention for domestic violence and abuse

Abstract: Background: Health services are often the first point of professional contact for people who have experienced domestic violence and abuse. We report on the evaluation of a multi-site, hospital-based advocacy intervention for survivors of domestic violence and abuse. Independent Domestic Violence Advisors (IDVAs), who provide survivors with support around safety, criminal justice, and health and wellbeing, were located in five hospitals in England between 2012 and 2015 in emergency departments and maternity ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 23 publications
(41 reference statements)
0
34
0
5
Order By: Relevance
“…[10] Furthermore, abuse often remains hidden, even when victims access healthcare, for example, victims often present seeking help for associated conditions, such as mental health problems, or physical injuries, caused by DVA, without disclosing it. [3,7,11,12] The factors in uencing non-disclosure are complex and include shame and embarrassment among victims, in addition to: lack of time, awareness, con dence, and skills/training amongst healthcare professionals. [3,7,11,12] Thus, there is a need to improve rates of identi cation of DVA, in healthcare, as well as the response when it is disclosed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[10] Furthermore, abuse often remains hidden, even when victims access healthcare, for example, victims often present seeking help for associated conditions, such as mental health problems, or physical injuries, caused by DVA, without disclosing it. [3,7,11,12] The factors in uencing non-disclosure are complex and include shame and embarrassment among victims, in addition to: lack of time, awareness, con dence, and skills/training amongst healthcare professionals. [3,7,11,12] Thus, there is a need to improve rates of identi cation of DVA, in healthcare, as well as the response when it is disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…[3,7,11,12] The factors in uencing non-disclosure are complex and include shame and embarrassment among victims, in addition to: lack of time, awareness, con dence, and skills/training amongst healthcare professionals. [3,7,11,12] Thus, there is a need to improve rates of identi cation of DVA, in healthcare, as well as the response when it is disclosed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An evaluation of an Independent Domestic Violence Advisor (IDVA) hospital programme found that staff sought advice for themselves personally even though the IDVA was there to support patients. 11 Evaluation of DA training for healthcare professionals (HPs) found ‘ an unintended consequence was the disclosure of DA among staff’ , highlighting a need for support mechanisms for staff. 12 It is important to understand doctors’ experience of DA to help employers, colleagues, and HPs respond positively, and to understand how aspects of working as a doctor may increase the risk of becoming a victim-survivor.…”
Section: Introductionmentioning
confidence: 99%